Mechanism-Based Pharmacokinetic Model for the Deglycosylation Kinetics of 20(S)-Ginsenosides Rh2 - Ren, Hong-can; Sun, Jian-guo; A, Ji-ye; Gu, Sheng-hua; Shi, Jian; Shao, Feng; Ai, Hua; Zhang, Jing-wei; Peng, Ying; Yan, Bei; Huang, Qing; Liu, Lin-sheng; et al. (Frontiers in Pharmacology, 2022)
Aim The 20(S)-ginsenoside Rh2 (Rh2) is being developed as a new antitumor drug. However, to date, little is known about the kinetics of its deglycosylation metabolite (protopanoxadiol) following Rh2 administration. The aim of this work was to (i) simultaneously characterise the pharmacokinetics of Rh2 and protopanoxadiol following intravenous and oral Rh2 administration, (ii) develop and validate a mechanism-based pharmacokinetic model to describe the deglycosylation kinetics and (iii) predict the percentage of Rh2 entering the systemic circulation in protopanoxadiol form. Method Plasma were collected from rats after the I.V. or P.O. administration of Rh2. The plasma Rh2 and protopanoxadiol concentrations were determined using HPLC-MS. The formation of protopanoxadiol, including acid degradation and metabolism of protopanoxadiol via microflorae, were integrated into the mechanism based pharmacokinetic model to describe the pharmacokinetics of Rh2 and protopanoxadiol simultaneously at 10 mg/kg. The concentration data collected following a 20 mg/kg dose of Rh2 was used for model validation. Results Following Rh2 administration, protopanoxadiol exhibited high exposure and atypical double peaks. The model described the abnormal kinetics well and was further validated using external data. Total 11% of the administered Rh2 was predicted to be transformed into PPD and enter systemic circulation after I.V. administration of Rh2, and total 20% of Rh2 be absorbed into the systemic circulation in protopanoxadiol form after P.O. administration of Rh2. Conclusion The developed model provides a useful tool to quantitatively study the deglycosylation kinetics of Rh2 and thus, provides a valuable resource for future pharmacokinetic studies of glycosides with similar deglycosylation metabolism.